Sociocultural Significance of the Phatic Function - Drazdauskienė, Marija Liudvika (Problemos, 1980)
Referring to the original idea of the phatic function as the use of language not to express thought, the present paper treats the phatic function in terms of its sociocultural significance. The purport of the phatic function being heterogeneous (sociability, the forecast of information, gratification, self-protection, identification of social status and ethnic properties, camouflage, word terror, etc.), it is found to reflect the sociocultural tradition of a community and to have considerable influence on the communicative function and social relations in general.